2023
DOI: 10.1371/journal.pntd.0011054
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a diagnostic device, CL Detect rapid test for the diagnosis of new world cutaneous leishmaniasis in Peru

Abstract: Background Cutaneous leishmaniasis (CL) is a neglected disease and a public health problem in Latin America. The diagnosis of CL in poor hyperendemic regions relies to large extent on the identification of amastigotes in Giemsa-stained smears. There is an urgent need for a rapid, sensitive and low cost diagnostic method for use in field conditions for CL as current modalities are not readily available. The primary objective of this study was to determine the sensitivity and specificity of the FDA-cleared CL De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Our findings align with very few studies that targeted CL diagnostic costs rather than determining only the test’s accuracy. Indeed, the studies from Peru and Sri Lanka agreed on the need for low-cost CL diagnostic tests, defined (as 4–5 USD per test) [ 12 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings align with very few studies that targeted CL diagnostic costs rather than determining only the test’s accuracy. Indeed, the studies from Peru and Sri Lanka agreed on the need for low-cost CL diagnostic tests, defined (as 4–5 USD per test) [ 12 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its performance compared to microscopy was slightly less sensitive than PCR tools as the gold standard [ 9 11 ]. A recent study from Peru using modified sampling scraping techniques found CL Detect Rapid Test sensitivity compared to microscopy with (64%) scenarios where the sample was collected using a dental broach and became (83%) when the sample was collected by Lancet [ 12 ]. However, in positive subjects confirmed by PCR for CL Detect Rapid Test and collected by scraping, microscopy had 08 false negative cases 108 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positivity rates were similar, Ct values were correlated, and good concordance was seen between most patients, with discrepancies in negative results likely caused by parasite distribution and inconsistent sample collection. Dental broach was previously studied in combination with the CL Detect Rapid test, which showed that using the rapid test on a dental broach had lower sensitivity than skin slit [ 21 , 24 ]. Dental broach was also shown to be promising as a sampling tool for loop-mediated isothermal amplification, where it reached a sensitivity of 94%, with PCR on dental broach in combination with skin slit microscopy as a reference test [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, our study of population genetics and distribution of L. (V.) braziliensis in Peru was possible after the identification of the parasites [81]. Other studies where we evaluated two different types of rapid tests took advantage from the identification of Leishmania species for inclusion criteria such as one study that tested RPA-LF [23,82] and another on the CL-Detect device [83] both to be applied under field conditions. It should be noted that an additional advantage of our procedure is that the samples can be included in absolute ethanol at room temperature and thus be sent without the need for cold chain from the sampling sites to the laboratory where the molecular assays are carried out.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%